To the approximate size of the nuclear region occupied by nucleolar bodies during cell differentiation and maturation using the human leukemic granulocytic lineage as a convenient model - Smetana, Karel; Klamová, Hana; Mikulenková, Dana (Physiological research, 2019)
The present study was undertaken to estimate the approximate size of nuclear regions occupied by nucleolar bodies during the cell differentiation and maturation. The differentiation and maturation of human leukemic granulocytic cells in patients suffering from the chronic phase of the chronic granulocytic leukemia (CML) represented a convenient model for such study because of the large number of cells for the diameter measurements at the single cell level. Early and advanced differentiation or maturation stages of these cells are well defined and nucleolar bodies and nuclear outlines are easily seen by simple cytochemical methods for the visualization of RNA and silver stained proteins in smear preparations. During the cell differentiation and maturation, the estimated size of the nuclear region occupied by nucleolar bodies decreased in both untreated and treated patients with the anti-leukemic therapy. However, the size reduction of nucleolar bodies in differentiated and mature cells was larger than that of the nucleus. In addition, the results also indicated that the nuclear region occupied by nucleolar bodies was characteristic for each differentiation and maturation stage of the granulocytic cell lineage and was not substantially influenced by the anti-leukemic therapy of CML patients.
Keywords: Cell Differentiation; granulocyty; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; buněčný rodokmen; lidé; buněčná diferenciace; Humans; chronická myeloidní leukemie; Cell Lineage; Granulocytes; buněčné jadérko; Cell Nucleolus